ANALISIS HUBUNGAN FAKTOR FISIOLOGIS DAN PSIKOLOGIS TERHADAP PRODUKTIVITAS PEKERJINDUSTRI PT. XYZ - Eka Rizki Pratama, - (2019)
PT. XYZ is committed to making food packaging as the best choice in Jakarta and its surrounding areas. Job activities in PT. XYZ also requires physical workload, mental workload and productivity level since most of the work activities are still done by human labor, from material inspection activities, work-environment cleaning activities, equipment maintenance activities, data productivity testing activities, to activities the incorporation of materials into a finished product that has a sale value. So need to do research on productivity level, whether influenced by physical work and work load of worker mental. Physical workload measurements were performed using total metabolic measurements, while measuring the mental workload using the NASA TLX method and measuring worker productivity. Further analyzing the relationship between physical workload and mental workload on work productivity of production workers of PT. XYZ. The calculation result shows that all divisions get high level of physical work load and mental work load. Results of processing with SPSS software for a series of statistical tests is a significant relationship between physical workload and mental workload on work productivity, or it can be said that the workload of physiology and psychology too have an effect on work productivity of workers